Reflection The thought of the Islamic Reform School in Tafsir Khal (An analytical descriptive study) - Saleh, Prof. Dr. Aras Muhammad (Sulaimani Journal for Humanities, 2023)
The impact of the Islamic reform school on Sheikh Muhammad Al-Khal's understanding of Al-Khal is the subject of this study. The researcher describes the Islamic reform school and outlines the main tenets of its approach to Islamic reform and social transformation in the first part. The concepts of the reform school and their effect on Sheikh Muhammad Al-Khal's writings in general and Al-Khal's interpretation in particular are discussed in the second section. The final section highlights the key conclusions that the researcher came to after examining Al-Khal's interpretation and discusses Al-Khal's technique in social change and the rebirth of Islamic philosophy.